Avaliar trabalhos visuais na escola : entre inquietações e experimentações surgem as fichas avaliativas - Siebert, Emanuele Cristina (2018)
The evaluative forms emerge from the need to evaluate the practical work done by the students in the art classes, based on objective criteria and thus avoiding that the evaluation was veiled or based on the teacher’s personal tastes. The narrative dialogues with Hernandez (2000), who approaches the evaluation in the teaching of the visual arts and with Bourdieu (2007) that reinforces the importance of art in school and the accomplishment of practical works. The report contextualizes the school scenario in which the proposal was experienced and how the form was structured, and all items arose from needs observed in the classroom, some items of organizational, disciplinary and other characteristics reinforcing the contents studied. The evaluative forms made evaluations faster and more objective, facilitating the dialogue between teacher and students, guiding and enabling the work could be corrected or redone if the student chooses